Palmitoyl Protein Thioesterase 1 Is Essential for Myogenic Autophagy of C2C12 Skeletal Myoblast - Yun, Hyeong Rok; Jo, Yong Hwa; Kim, Jieun; Nguyen, Ngoc Ngo Yen; Shin, Yoonhwa; Kim, Sung Soo; Choi, Tae Gyu (Frontiers in Physiology, 2020)
Skeletal muscle differentiation is an essential process for the maintenance of muscle development and homeostasis. Reactive oxygen species (ROS) are critical signaling molecules involved in muscle differentiation. Palmitoyl protein thioesterase 1 (PPT1), a lysosomal enzyme, is involved in removing thioester-linked fatty acid groups from modified cysteine residues in proteins. However, the role of PPT1 in muscle differentiation remains to be elucidated. Here, we found that PPT1 plays a critical role in the differentiation of C2C12 skeletal myoblasts. The expression of PPT1 gradually increased in response to mitochondrial ROS during muscle differentiation, which was attenuated by treatment with antioxidants. Moreover, we revealed that PPT1 transactivation occurs through nuclear factor erythroid 2-regulated factor 2 (Nrf2) binding the antioxidant response element (ARE) in its promoter region. Knockdown of PPT1 with specific siRNA disrupted lysosomal function by increasing its pH. Subsequently, it caused excessive accumulation of autophagy flux, thereby impairing muscle fiber formation. In conclusion, we suggest that PPT1 is factor a responsible for myogenic autophagy in differentiating C2C12 myoblasts.